Incorporating citronella oil into edible coating to extend the stable life and improve the quality of banana fruit - Iqbal Kamar; Dewi Yunihharni (Jurnal Pijar Mipa, 2023)
Carboxymethyl cellulose (CMC) is a linear polysaccharide with long chains soluble in water and anionic. It exhibits high viscosity and possesses non-toxic and non-allergenic properties. The use of plant-based essential oils in edible films to replace vegetable oils, cereals, or seeds. One essential oil with good antibacterial activity is the oil derived from citronella leaves. The main components of this citronella oil compound consist of citronellal, citronellol, and geraniol, which can inhibit bacterial activity. Therefore, it is necessary to develop technology for handling fresh fruits to inhibit excessive ripening and decay. This can be achieved by creating an edible coating with essential oils. This study aims to investigate the impact of using an edible covering (carboxymethyl cellulose) incorporated with lemongrass oil on the storage of bananas. The experimental design employed in this study utilized a Completely Randomized Design (CRD) with one factor, namely citronella oil (0.3%, 0.6%, and 0.9%), as well as the application of edible coating with two elements, namely treatment variations (layer and non-coating) and storage duration (day 0 to day 15). The storage process is conducted until ripening occurs in banana fruits for 16 days, with daily observations. Throughout the storage procedure, various metrics were monitored in bananas, including weight loss, acidity level (pH), and total plate count (TPC). The research findings indicate that the highest weight loss of banana fruit is observed in bananas without edible covering, amounting to 13.10%. Conversely, bananas with edible coating and 0.5% lemongrass oil exhibit a lower weight loss of 7.35%. The application of edible coating significantly impacts the increase in pH and total microbial growth on banana fruits.